Formulation Ointment Preparation Leaf Extract EthanolKirinyuh ( Euphatorium Odoratum L. ) AsHealer Open Wound In Rabbit - Arif, Muchammad Zein, Tanti Azizah S, M.Sc.,Apt, Suprapto, M.Sc.,Apt (2016)
Kirinyuh is a family of Asteraceae that containing flavonoids, saponins and tannins which is having effect for heal wounds. The purpose of this research is to knowing the activities of kirinyuh leaf extract ointment to heal wounds at rabbits and also for determine the effect variation of concentrations of ethanol extract of the leaves kirinyuh against physical Properties ointment. Kirinyuh leaf extract is macerated and variated kirinyuh leaf ethanol extract with a concentration 2.5%, 5% and 10%. Which is formulated with adeps lanae ointment. Ointment preparation tested include organoleptic physical properties, pH, viscosity, Spreadability and adhesiveness. The ointment preparation is applied on rabbit back which has been hurt as much as 6 wound locations.That positive control, negative control, in control, ointments kirinyuh leaf extract ethanol concentration of 2.5%, 5% and 10%. The result is the wound healing was analyzed by Shapiro-Wilk test then continued by one way Anova test followed by a level of 95%. The result showed that the variation of the concentration of ethanol extract of the leaves kirinyuh 2.5%, 5% and 10% at ointment preparation have not affects the physical properties of the ointment preparation viscosity, adhesiveness and spreadability. The results obtained indicate ointment ethanol extract of the leaves kirinyuh not having an activity as a wound healer rabbit open at Anova value is 0.225 (p> 0.05).